The Continuing Paradox of Traditional Female and Male Circumcision among Kuria in Northeastern Tanzania - Mhando, Nandera Ernest (Anthropologica, 2018)
Using participant observation, life histories, narratives, interviews and telephone conversations, this article explores reasons behind the failure of anti-female circumcision and anti-traditional male circumcision campaigns among the Kuria, an ethnic community based in Northeast Tanzania. Besides circumcision being central to attaining full personhood in the traditional society, undergoing this ritual has far-reaching socio-economic and political implications for both males and females, including gaining access to resources, political positions and socio-economic support. Despite fierce opposition to female circumcision from state and non-state actors, as well as social stigma, ridicule and sanctions against it, the practice, now in international language outlawed as female genital mutilation, goes on unabated. Similarly, despite the availability of modern health services for medical male circumcision, which has a high potential in limiting the spread of HIV/AIDS, Kuria boys resort to the traditional forms of circumcision. This article underscores the importance of understanding local discourse in a bid to eradicate circumcision with more informed means.